Sinc Collocation Solutions for the Integral Algebraic Equation of Index-1 (Advances in Applied Mathematics and Mechanics, 2018)
In this article, Sinc collocation method is considered to obtain the numericalsolution of integral algebraic equation of index-1 by reducing it to an explicit systemof algebraic equation. It is shown that Sinc collocation solution can produce an errorof order $\mathcal{O}(√Ne^{−k√N})$. Moreover, Sinc method is applied to several examples toillustrate the accuracy and implementation of the method.